LIQUEFACTION SYSTEM DESIGN USING HYDRAULIC MECHANISM - Muhammad Hardiman Nur Ramadhan; Resa Hardianto; Doohan Taqdissillah; Erwinda Fenty Anggraeni; Arfan (RADJA PUBLIKA, 2026)
Liquefaction is a natural disaster that cannot be predicted. Therefore a simulation tool is needed to determine the characteristics of the disaster, so that it can be reduced. This simulation tool moves on the x-axis and y-axis with the drive system using a hydraulic system. The purpose of this research is to measure the vibration parameters that arise in the liquefaction machine. In addition, to analyze the vibration system that arises in the liquefaction machine on the x-axis and y-axis. And the analysis method used is experiment. This mechanism is designed in 2 levels using 6 rollers on each floor. The speed and acceleration of the drive mechanism are able to describe the true state of liquefaction.